In silico analysis of the solute carrier (SLC) family in cancer indicates a link among DNA methylation, metabolic adaptation, drug response, and immune reactivity - Lavoro, Alessandro; Falzone, Luca; Tomasello, Barbara; Conti, Giuseppe Nicolò; Libra, Massimo; Candido, Saverio (Frontiers in Pharmacology, 2023)
The oncogenic transformation is driven by genetic and epigenetic alterations influencing cancer cell fate. These alterations also result in metabolic reprogramming by modulating the expression of membrane Solute Carrier (SLC) transporters involved in biomolecules trafficking. SLCs act as tumor suppressors or promoters influencing cancer methylome, tumor growth, immune-escape, and chemoresistance. This in silico study aimed to identify the deregulated SLCs in various tumor types compared to normal tissues by analyzing the TCGA Target GTEx dataset. Furthermore, the relationship between SLCs expression and the most relevant tumor features was tackled along with their genetic regulation mediated by DNA methylation. We identified 62 differentially expressed SLCs, including the downregulated SLC25A27 and SLC17A7, as well as the upregulated SLC27A2 and SLC12A8. Notably, SLC4A4 and SLC7A11 expression was associated with favorable and unfavorable outcome, respectively. Moreover, SLC6A14, SLC34A2, and SLC1A2 were linked to tumor immune responsiveness. Interestingly, SLC24A5 and SLC45A2 positively correlated with anti-MEK and anti-RAF sensitivity. The expression of relevant SLCs was correlated with hypo- and hyper-methylation of promoter and body region, showing an established DNA methylation pattern. Noteworthy, the positive association of cg06690548 (SLC7A11) methylation with cancer outcome suggests the independent predictive role of DNA methylation at a single nucleotide resolution. Although our in silico overview revealed a wide heterogeneity depending on different SLCs functions and tumor types, we identified key SLCs and pointed out the role of DNA methylation as regulatory mechanism of their expression. Overall, these findings deserve further studies to identify novel cancer biomarkers and promising therapeutic targets.